Pengaruh Pelayanan Publik, Kualitas Kehidupan Kerja, dan Integritas terhadap Kinerja Aparatur Desa Se-Kecamatan Bulakamba Kabupaten Brebes - Agustian Nur Alif; Slamet Bambang Riono; Ari Kristiana; Akbar NP Darma Wahana; Amelia Sholeha (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of public service, quality of work life, and integrity on the performance of village officials in Bulakamba District, Brebes Regency. A quantitative approach was used with a survey method. The population in this study consisted of all 149 village apparatus employees in Bulakamba District. The sample size was determined using the Slovin formula with a 5% margin of error, resulting in 109 respondents selected based on the criteria of being over 17 years old and having at least one year of work experience. Data were collected through the distribution of questionnaires and analyzed using multiple linear regression. The results of the study show that public service has a positive and significant effect on the performance of village officials. The quality of work life also has a positive and significant effect, indicating the importance of a supportive work environment. In addition, integrity has been proven to have a positive and significant impact on performance, emphasizing that honesty and responsibility are crucial factors in improving work outcomes. Simultaneously, public service, quality of work life, and integrity jointly contribute 45.00% to the performance of village officials, while the remaining 55.00% is influenced by other variables not examined in this study.